Myth and Religion: A Comparative Analysis of the Ideologies of the Mahdist and Maji Maji Anti-Colonial Resistance Movements in Sudan and Tanganyika (1881-1907) - Araya, Asrat (Ethiopian Journal of Social Sciences, 2023)
The second half of the nineteenth century witnessed European massive expansion andcolonization of Africa. Based on its nature, African reaction to European colonial expansioncan broadly be divided into non-violent and violent armed resistance movements. Mahdist andMaji Maji movements were among the famous African armed responses against colonialism.They were inspired and guided by traditional ideologies of religion and myth. Comparativeanalysis on the traditional ideologies of African resistance movements is scant. This study aimsat comparing the ideological attributes of the Mahdist and Maji Maji anti-colonial resistancemovements in Sudan and Tanganyika. Its main purpose is to give insights into the underlingfeatures of the ideologies of the two African resistance movements. This work entirely dependson secondary sources. Qualitative approach is employed to collect data. An integratedqualitative data analysis approach (thematic and chronological) and exposition, complimentedby narrative and descriptive, mode of historical data synthesis is used in this paper. Aninvestigation of the available sources indicates that Africans had well developed traditionalideologies, mainly mixes of local and regional experiences and beliefs, whereby they efficientlyreacted to colonial domination. The ideologies were strong enough to unite and mobilize theSudanese and Tanganyikan diverse ethnic, tribal, religious, social, and economic disparities.The two movements share common features as manifested in motivations, methods ofideological reconstruction, and mobilization. However, they are quite different in their vision,level of implementation, and end results. The research work is expected to give new insights forfurther research works aiming at decolonizing European racist literature that depicts theAfrican anti-colonial resistance movements as spontaneous, barbaric, uncivilized, andprimitive troubles to European civilized mission towards Africa.